Sexual Assault, Female Immigrant Victims, and Judicial Focal Concerns in U.S. and Canadian Courts - Hashmi, Sidra (American journal of criminal justice, 2025)
This study draws on the focal concerns perspective to explore the persistence of rape myths in U.S. and Canadian court cases involving immigrant women survivors. Results from qualitative content analysis of judicial rhetoric in both countries from 1996 to 2021 reveal a nuanced picture. Notably, judges reinforced some rape myths by, for example, being less likely to uphold convictions in cases that did not involve weapons or that occurred in private settings. However, judges challenged rape myths, with some judges explicitly considering the vulnerability of immigrant women, further contributing to the complexities of their decision-making process.